Property Right, Regulation and Economic Growth - Majid Sameti; Rohollah Shahnazi; Zahra dehghan shabani (فصلنامه پژوهش‌های اقتصادی ایران, 2010)
This paper investigates the role of property right and regulation in credit, business and labor markets on economic growth by using two panel data models for 80 countries during 2000-2005. The first model considers legal structure and total effect of regulation on economic growth and the second model investigates three main component of regulation; i.e. regulation in credit, business and labor markets and property right on economic growth. findings of the first model show labor force, human capital, capital stock, property right and regulation have positive effect on economic growth. And according to the second model property right and regulation in credit and labor markets have positive effect on economic growth.